2020
DOI: 10.1021/acs.jafc.0c00212
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Gastrointestinal Digestion of Palm Olein and Palm Stearin-in-Water Emulsions with Different Physical States and Fat Contents

Abstract: The impacts of lipid physical state and content on lipid digestion behavior were investigated using 4 and 20% palm olein-in-water emulsions (4% PO and 20% PO) and 4 and 20% palm stearin-in-water emulsions (4% PS and 20% PS). The changes of lipid physical state, particle size, and microstructure during gastrointestinal digestion; the free fatty acid (FFA) released in the intestinal phase; and the fatty acid composition of micellar phases were investigated. After gastric digestion, all emulsions underwent floccu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
(87 reference statements)
0
30
0
Order By: Relevance
“…The D [3,2] of 20S was significantly larger than that of 30S, but both of them were significantly smaller than 20L ( P < 0.05, Figure e). Wan et al observed a similar phenomenon: the particle size of 4% solid palm stearin was smaller than that of 4% liquid palm olein after gastric digestion . They inferred that solid fat had a low effect on the stability of the emulsion, which might not be accurate.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The D [3,2] of 20S was significantly larger than that of 30S, but both of them were significantly smaller than 20L ( P < 0.05, Figure e). Wan et al observed a similar phenomenon: the particle size of 4% solid palm stearin was smaller than that of 4% liquid palm olein after gastric digestion . They inferred that solid fat had a low effect on the stability of the emulsion, which might not be accurate.…”
Section: Resultsmentioning
confidence: 94%
“…Milk fat is mainly composed of saturated FA (approximately 65%) and long-chain FA (approximately 82%), which contributes to its melting temperature being slightly lower than the human body temperature (37 °C). , Nevertheless, temperature fluctuations during dairy processing can change the polytypism and polymorphism of milk fat. , The polymorphic evolution (subcell structures: unstable α-polymorph → stable β-polymorph) and molecular rearrangement (stacking geometries: unstable 3L arrangement → stable 2L arrangement) caused by crystallization and recrystallization lead to the formation of high-melting-temperature fractions. The melting temperature of these fat fractions is higher than the human body temperature and exists as a solid in the gastrointestinal tract (GIT). Generally, high-melting-temperature lipids containing solid fat at body temperature tend to have a lower digestibility and bioavailability compared with liquid oils, which was verified by in vitro , , animal, and human , studies. On the one hand, these solid TAG fractions, which are mainly composed of long-chain saturated FAs, have the problem of being indigestible and the risk of inducing cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations